Cor Triatriatum Dexter: An Innocent Bystander - Stephanie C. Fuentes Rojas; Gerald Lawrie; Nadeen N. Faza (Methodist DeBakey Cardiovascular Journal)
Cor triatriatum dexter is a rare congenital heart defect with a varied clinical presentation ranging from asymptomatic to right heart failure. Accurate diagnosis is imperative as it may affect clinical decision making. We present a multimodality imaging assessment of cor triatriatum dexter in a 70-year-old woman with severe tricuspid regurgitation.